Impact of curriculum Differentiation on Students’ interest in English Language in Secondary Schools - Augusta Chiedu Assimonye; Chinasa Florence Okoh (PT. Pusmedia Group Indonesia, 2025)
This study employed a descriptive survey design to examine teachers’ perceptions of curriculum differentiation in English Language teaching. The population comprised secondary school English teachers, from which 194 respondents (90 male and 104 female) were selected using stratified random sampling. Data were collected with a validated questionnaire, Curriculum Differentiation in English Language Teaching Scale (CDELT), structured on a four-point Likert scale. Validity was ensured by expert review, while reliability was confirmed with a pilot test yielding a Cronbach Alpha of 0.82. Data were analyzed using SPSS version 25, applying descriptive statistics for research questions and ANOVA for hypothesis testing. The study involved 194 English Language teachers, comprising 90 males (46.4%) and 104 females (53.6%). Findings on curriculum differentiation strategies revealed mean scores of 3.18 for males and 3.25 for females, suggesting both genders moderately apply differentiation in teaching. Regarding its influence on students’ interest, male teachers reported a mean of 3.18 while females scored slightly higher at 3.25, indicating similar perceptions. For challenges faced, male teachers scored 2.97 compared to 3.09 for females, showing females perceived greater challenges. ANOVA results indicated significant gender differences in curriculum differentiation application (p = .008) and challenges (p = .048), but not in perceived influence on students’ interest (p = .370). The study concludes that curriculum differentiation is essential for enhancing students’ interest in English Language learning, but its effective implementation requires greater teacher support and training. Recommendations were made for capacity building, provision of instructional resources, and policy reinforcement to strengthen differentiated instructional practices.